Thrilling travel or lonesome long haul? Loneliness and acculturation behavior of adolescents studying abroad. (July 2021) - Serrano-Sánchez, Juan; Zimmermann, Julia; Jonkmann, Kathrin
Abstract: Studying abroad far away from family and friends may put young people at particular risk of experiencing loneliness. From this perspective, behavioral strategies to deal with the challenges of a new living environment have important implications for the development of loneliness over the course of an educational stay abroad. This study investigates adolescents' experience of loneliness over the course of a school year abroad, as well as the longitudinal interplay between loneliness and the sojourners' host- and home-cultural behavioral engagement. To that end, we analyzed data from 1, 225 student sojourners using latent growth curve models and cross-lagged panel models. Participants were surveyed four times before and during the student exchange period using online questionnaires. Our results showed that loneliness increased during the transition from home to the host country but decreased again afterwards. Host-cultural behavioral engagement predicted lower levels of loneliness by a direct effect, whereas home-cultural behavioral engagement predicted higher levels of loneliness by a time-lagged indirect effect via host-cultural behavioral engagement. Implications for acculturation and loneliness research, and practical implications for the support of student sojourners are discussed.